Student Association and Its Relation to The Mental Health of Secondary Vocational Chinese School Students Towards the Design of An Intervention Program - Shujuan Zhao (International Journal of Management and Education in Human Development, 2022)
Secondary vocational school students are still in adolescence, which is a critical period for the formation of values and world views. With the long-term academic performance of secondary vocational students which is not ideal, the mental health status of students is worrying, thus the formation of secondary vocational student mental health intervention project has become an important subject of secondary vocational schools. Students' associations in secondary vocational schools are under the unified management of the school, with teachers participating in guiding all the students who are participating in the student organizations. Students' associations are a platform for students to realize self-knowledge and self-adjustment, also a good way for schools to carry out mental health education. This study investigated the mental health of secondary vocational school students in Taiyuan City, Shanxi Province, China in the school year 2019, and further explored the relationship between the involvement of secondary vocational school students in student associations and their mental health. On this basis, an effective mental health intervention plan for secondary vocational school students was proposed which would provide the theoretical and practical guidance for the development and promotion of secondary vocational school student associations and student mental health education.